Hydroxyapatite-reinforced alginate fibers with bioinspired dually aligned architectures. (1st September 2021) - Wan, Fuqiang; Ping, Hang; Wang, Wenxuan; Zou, Zhaoyong; Xie, Hao; Su, Bao-Lian; Liu, Dabiao; Fu, Zhengyi
Abstract: Biological materials have excellent mechanical properties due to their organized structures from nano- to macro-scale. Artificial manufacture of materials with anisotropic microstructures still remains challenging. We described a stress-induced method to fabricate anisotropic alginate fibers. Organic-inorganic composite fibers were obtained by incorporating aligned hydroxyapatite (HAP) nanowires into the alginate fiber. Detailed structural characterization revealed the bone-like structure of the HAP-reinforced alginate fibers. Tensile test results showed that the maximum Young's modulus and tensile strength were 4.3 GPa and 153.8 MPa, respectively. A multiscale reinforcing mechanism is proposed after the discussion of the structure-property relationship: highly ordered and compacted nanofibrils aligned along the longitudinal direction at the microscale, and two kinds of alginate gels with different mechanical behaviors at the nanoscale coexisted (acidic alginate gel and calcium-alginate gel). This work validates the effectiveness of the bioinspired fabrication strategy, which inspires further manufacturing and optimization of materials for diverse applications. Highlights: A highly anisotropic alginate fiber was fabricated by spin-coating. Acidic alginate and a calcium-alginate gel structure coexist in the fiber. Bone-like fibers were obtained after incorporation of aligned hydroxyapatite. Structure-property relationships were discussed in detail and in-depth.